Novel alkynyl-containing phosphonate ester oligomer with high charring capability as flame retardant additive for thermoplastic polyurethane. (15th October 2020) - Chen, Hong; Deng, Cong; Zhao, Ze-Yong; Huang, Sheng-Chao; Wei, Yun-Xia; Wang, Yu-Zhong
Abstract: Phosphonate esters may be used as flame retardants for flammable polymers, but always face low flame-retardant efficiency and melt dripping. Until now, no remarkable progress was made in solving the above two defects, thus tremendously affecting their applications as flame retardants. In current work, from the chemistry viewpoint, we designed and synthesized poly(2-butyne-1, 4-diol phenylphosphonate) (PPBP) containing alkynyl group to break through above-mentioned defects. Compared with the corresponding control sample poly(1, 4-butanediol phenylphosphonate) (PPBOP) without alkynyl, thermal analysis revealed that residual char of the PPBP with CC bonds increased to 45.0%, much higher than 1.6% for the PPBOP without CC bonds, and greatly increased by 27 folds. Various measurements and kinetic analysis were used to investigate the underlying cause for the leap in charring. It turns out that PPBP was involved in a unique decomposing and crosslinking process upon heating, which played a vital role in the leap in charring for PPBP. The leap in charring might afford polymers better flame retardancy through condensed phase. After incorporation of the PPBP into thermoplastic polyurethane (TPU), burning tests illustrated that PPBP not only endowed TPU with excellent flame retardancy and anti-melt dripping performance, but also resulted in extremely low heat release rate and smoke production rate, correspondingly decreased by 70.7% and 53.9% compared with those of TPU. Various measurements further confirmed that the charring caused by PPBP itself and the enhanced charring of TPU induced by PPBP played a crucial role in the remarkable superior flame retardancy of TPU/PPBP.